Conservative treatments for women with stress urinary incontinence: a systematic review and network meta-analysis - Mengzhen Li; Mengzhen Li; Kexin Qiu; Kexin Qiu; Haoran Guo; Haoran Guo; Mengsi Fan; Mengsi Fan; Li Yan; Li Yan (Frontiers in Medicine)
ObjectiveThis study aimed to compare the effectiveness of various conservative treatment strategies for women with stress urinary incontinence.MethodsA comprehensive search of PubMed, Web of Science, Embase, and the Cochrane Library was conducted from their inception through March 2024, without restrictions on language or location. Randomized controlled trials (RCTs) comparing the efficacy of conservative treatments for stress urinary incontinence, using short-term pad test or the International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQ-UI SF) score as outcome measures, were included. We conducted a network meta-analysis using a random-effects model to compare the effectiveness of different conservative treatment strategies, employing prediction interval plots and league tables, and ranked them according to the surface under the cumulative ranking curve (SUCRA). The quality of the included studies was assessed following the Cochrane Handbook for Systematic Reviews of Interventions.ResultsA total of 31 RCTs involving 1,900 patients across 8 intervention categories were included in the analysis. SUCRA rankings indicated that electrical stimulation (SUCRA = 95.9%) was the most effective therapy for improving ICIQ-UI SF scores, followed by biofeedback electrical stimulation (SUCRA = 84.9%), radiofrequency (SUCRA = 77.5%), biofeedback (SUCRA = 57.8%), magnetic stimulation (SUCRA = 45.3%), pelvic floor muscle training (SUCRA = 38.4%), Er: YAG laser (SUCRA = 37.4%), and CO2 laser (SUCRA = 7.4%). In terms of reducing urine leakage, the treatments were ranked in descending order as follows: Er: YAG laser (SUCRA = 97.5%), biofeedback electrical stimulation (SUCRA = 83.4%), biofeedback (SUCRA = 67.0%), radiofrequency (SUCRA = 59.5%), electrical stimulation (SUCRA = 48.4%), pelvic floor muscle training (SUCRA = 43.0%), magnetic stimulation (SUCRA = 27.8%), and CO2 laser (SUCRA = 21.4%). Based on the clustered rankings of the two metrics, biofeedback electrical stimulation was identified as the most effective therapy for improving stress urinary incontinence.ConclusionBased on the combined analysis of two indicators, we found that biofeedback electrical stimulation may be the optimal therapy for the conservative management of stress urinary incontinence.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024569845.